App-based intervention for children with reading difficulties : a description of five cases - Kaplan, Gaby (University of Cape Town, 2015)
Includes bibliographical references. === This descriptive single subject intervention study aimed to describe the outcomes of an application (app)-based intervention for five children with reading difficulties. All participants were required to have a grade one reading level. Each participant’s language and literacy profiles are detailed in accordance with developmental and information processing models, and intervention was designed based on each child’s specific level of difficulty. Following a baseline control period, each child received approximately six weeks of intervention using the Reading TherAppy and/or Comprehension TherAppy app (Tactus Therapy Solutions) on an iPad ® mini, which was mediated by the researcher on a 1:1 basis. Treated and untreated probe items were administered at three points in the study (baseline, pre, post) in order to determine the effects of intervention on treated and untreated, matched items. Each child’s reading on standardized literacy measures was re-evaluated post intervention. This was followed by an interview with each participant to obtain information about his or her experience of the intervention. Results show that all participants improved their reading of items treated in the intervention. In addition, some of the participants’ standardized reading and spelling scores improved in relation to typically developing peers from pre to post intervention testing. Changes are detailed for each participant using the theoretical models. Child interviews indicated that all children enjoyed a positive experience of intervention. This study aimed to explore and contribute to the limited knowledge base on efficacy, optimal dosage and outcomes of app-based intervention for children with reading difficulties. The implications of the study are discussed in relation to Speech Language Therapists working in educational settings, the functional application of models of reading, and the reading intervention literature.